1979
DOI: 10.1093/bja/51.6.551
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Changes Following Induction of Anaesthesia With Etomidate in Patients With Cardiac Disease

Abstract: The cardiorespiratory effects of etomidate were measured in two groups of six patients with aortic or mitral valve disease. The induction of anaesthesia with etomidate 0.3 mg kg-1 was followed by a second dose 10 min later. After the first dose, a 19% decrease in systemic arterial pressure was associated with a decrease in systemic vascular resistance and left ventricular heart work. Cardiac index, pulmonary artery pressure and wedge pressure all decreased slightly. Central venous pressure and heart rate did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Values only became significantly lower than the control values during the 2nd minute after the induction, [30] which may have resulted in an increase of approximately 15% of PaCO 2 but unchanged PaO 2 . [31] In this trial, as the dosage of propofol increased, the probability of respiratory and cardiovascular depression also increased, which was similar to a previous study. [32] Numerous studies have found that propofol can reduce blood pressure by suppressing sympathetic activity, inhibiting myocardial contractility, and dilating blood vessels.…”
Section: Discussionsupporting
confidence: 89%
“…Values only became significantly lower than the control values during the 2nd minute after the induction, [30] which may have resulted in an increase of approximately 15% of PaCO 2 but unchanged PaO 2 . [31] In this trial, as the dosage of propofol increased, the probability of respiratory and cardiovascular depression also increased, which was similar to a previous study. [32] Numerous studies have found that propofol can reduce blood pressure by suppressing sympathetic activity, inhibiting myocardial contractility, and dilating blood vessels.…”
Section: Discussionsupporting
confidence: 89%
“…Studies confirm that reduction of stress response in paediatric patients undergoing cardiac surgery helps improve postoperative morbidity. Etomidate [7][8][9] and ketamine are well known anaesthetic agents routinely used for induction of anaesthesia for paediatric cardiac surgeries. Hence, the study was conducted to compare the effect of anaesthetic induction with single dose etomidate versus ketamine, in paediatric patients undergoing Patent ductus arteriosus (PDA) ligation, on serum cortisol levels.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 It produces sedation and hypnosis by enhancing the function of γ-aminobutyric acid type A (GABA A ) receptors in the brain, an action that is highly dependent upon the receptor’s subunit composition 6 ; GABA A receptor’s containing β 2 or β 3 subunits are substantially more sensitive to the actions of etomidate than those containing β 1 subunits. 7 Among clinical anesthetics, such high selectivity is unusual and may account for distinguishing aspects of etomidate’s pharmacology, potentially including its tendency to produce myoclonus and lower seizure thresholds or maintain cardiovascular stability.…”
Section: Introductionmentioning
confidence: 99%